2018
DOI: 10.1186/s12885-018-4762-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of breast cancer on prospective memory functioning assessed by virtual reality and influence of sleep quality and hormonal therapy: PROSOM-K study

Abstract: BackgroundBreast cancer (BC) is the most frequent cancer in women with more than 70% of BC patients being treated with hormonal therapy (HT). Among these patients, some report difficulties in remembering what they are supposed to do at the right moment, referring to prospective memory (PM). PM is essential for autonomy and medical adherence of patients, and requires an ecological assessment. Virtual reality, that recreates naturalistic environment, seems to be a promising method to evaluate PM. Several BC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 48 publications
(50 reference statements)
0
22
0
Order By: Relevance
“…However, the type of cancer in each study differs considerably, as shown in Table II. Approximately, 23% of the papers were focused on breast cancer treatments [22], [23], [26], [27], [28], [31], [35], [37], [39], [41] followed by blood cancer (e.g., leukaemia, lymphoblastic, etc.) (12%) [21], [25], [33], [36], [38], bone cancer (12%) [25], [29], [33], [38], [40], and brain cancer (12%) [25], [32], [33], [38], [40].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the type of cancer in each study differs considerably, as shown in Table II. Approximately, 23% of the papers were focused on breast cancer treatments [22], [23], [26], [27], [28], [31], [35], [37], [39], [41] followed by blood cancer (e.g., leukaemia, lymphoblastic, etc.) (12%) [21], [25], [33], [36], [38], bone cancer (12%) [25], [29], [33], [38], [40], and brain cancer (12%) [25], [32], [33], [38], [40].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 12% of papers did not report the type of pain [20], [23], [32]. Some of the reviewed studies were not related directly to pain (35%), meaning that they, examined closely side effects such as fatigue, anxiety, depression, emotional distress, neurocognitive problems, prospective memory issues, and other issues that cancer patients are usually dealing with because of the procedural pain caused by the medical processes, [22], [28], [30], [33], [34], [35], [38], [40], [42].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One cognitive deficit is prospective memory (PM), which is the capability of memorizing things to be done at a certain time or place [ 9 ]. Prospective memory based on time (TBPM) and prospective memory based on event (EBPM) are distinguishable aspects of PM.…”
Section: Introductionmentioning
confidence: 99%